Sustainability Performance Evaluation System in Government A Balanced Scorecard Approach Towards Sustainable Development - Chai, Nan (Springer Netherlands : Imprint: Springer, 2009)
The principles of modern strategic management are illustrated by an ancient Chinese tale: a man who wanted to go south was in a carriage driving north. A passer-by asked him "If you are going to the south, why is your chariot heading north?" The man answered, "My horse is good at running, my driver is highly skilled at driving a carriage, and I have enough money." Like the Chinese journeyman, the success of today's organizations and programs not only depends on productivity (good-running horse), workforce capability (highly-skilled driver) and financial support (enough money), but is also determined by their strategic orientation. If the strategy and objectives setting errs from the original mission, operations will be inefficient and ineffective. Progressing towards sustainable development raises significant obstacles to governments wishing to conduct performance evaluations, because at present there are neither generally accepted methods nor specific standards to be met. This book, which evolved from an acclaimed doctoral dissertation, helps overcome these obstacles by developing a set of framework indicators employing a strategic and comprehensive approach called the "Sustainability Balanced Scorecard". As a conceptual basis for the further research and application, this volume will be essential reading for researchers and practitioners involved in environmental and sustainability issues, as well as public management and strategic control studies. Evaluators will find methodological approaches and applied tools for their work, while decision-makers and managers will find this text a valuable resource in managing social, economic and environmental issues in a balanced and integrated manner. Governments will also find it helpful in establishing an evaluation system for sustainable development.